Improving Automatic Position Reporting System (APRS) throughput and reliability - Van Tonder, Hendrik Petrus (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MScEng (Electrical and Electronic Engineering))--University of Stellenbosch, 2005.